AN INTEGRATED LEARNING MEDIA IN CHEMISTRY: HOW CAN IT HELP TEACHERS AND STUDENTS TO CREATE A GOOD IMPRESSION? - Sausan, Inas; Saputro, S; Indriyanti, N Y (Unnes Science Education Journal, 2019)
Most junior high school students considered chemistry as a complicated science subject with abstract symbols and terms that must be memorized. The difficulty of learning chemistry can make students have low positive perceptions of chemistry. The purpose of our multiple case study was to explore how an integrated learning media can help teachers and students understand the difficulty of chemistry and create a good impression in junior high school. The integrated learning media has been developed based on multiple representations in chemistry. The study was conducted in three classes in grade 7. Several techniques were used to collect the data: a classroom observation, a test, the questionnaires, and an interview. We documented that the appearance of integrated learning media could make the students attracted and curious about chemistry. They were interested in various bright colors used in integrated learning media, which captured their attention to focus on learning. The integrated learning media made it easier for the teacher to introduce chemistry through podcast, molymod, and simulation.